Bartolomé Bennassar y la historia moderna de España - Carlos Martínez Shaw (Les Cahiers de Framespa)
In the frame of an homage to the great historian and hispanist Bartolomé Bennassar, are analyzed his main productions in the field of Spanish an American Early Modern History (and first of all his masterpiece Valladolid el ses campagnes au Siècle d’Or published in 1967). At the same time, are evoked his human and professional profile and his lasting and hearty relationship with Spain.